Molecular cloning and characterization of the STE7 and STE11 genes of Saccharomyces cerevisiae. - Chaleff, D T (1985)
In the yeast Saccharomyces cerevisiae, haploid cells occur in one of the two cell types, a or alpha. The allele present at the mating type (MAT) locus plays a prominent role in the control of cell type expression. An important consequence of the elaboration of cell type is the ability of cells of one mating type to conjugate with cells of the opposite mating type, resulting in yet a third cell type, an a/alpha diploid. Numerous genes that are involved in the expression of cell type and the conjugation process have been identified by standard genetic techniques. Molecular analysis has shown that expression of several of these genes is subject to control on the transcriptional level by the MAT locus. Two genes, STE7 and STE11, are required for mating in both haploid cell types; ste7 and ste11 mutants are sterile. We report here the molecular cloning of STE7 and STE11 genes and show that expression of these genes is not regulated transcriptionally by the MAT locus. We also have genetically mapped the STE11 gene to chromosome XII, 40 centimorgans from ura4.